Use of Lactobacillus Bacteria to Degrade Oil and Grease in Restaurant Wastewater - Novirina Hendrasarie; Syahrul Romadon; RKH Putro; Aussie A. (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Restaurant wastewater poses a significant environmental challenge, especially concerning the removal of oil and grease, which is known to be highly persistent. To tackle this issue, the research utilized a Lactobacillus bacteria consortium to effectively degrade oil and grease present in the wastewater. The Lactobacillus bacteria consortium was applied in an aerobic environment within the Grease Trap, while various treatment conditions, such as hydraulic retention time (HRT) and aeration rate, were evaluated to determine the optimal settings for the SBR. By employing this combined pre-treatment and SBR approach, distinct aerobic and anaerobic conditions were created, leading to significant removal of pollutant parameters by microorganisms. Remarkably, the study’s findings demonstrated that at a 24-hour retention time and a 14 L/minute aeration rate, the Lactobacillus bacteria consortium achieved an impressive 97.42% removal of oil and grease, compared to only 84.54% removal by the Grease Trap without bacteria. The pretreatment of the Lactobacillus bacteria consortium led to even higher reductions in other pollutant parameters. By harnessing the power of the Lactobacillus bacteria consortium and employing the SBR in combination with pre-treatment, this approach holds great potential for addressing the persistent challenge of oil and grease removal in restaurant wastewater and improving overall water quality.